Hubungan Lingkungan, Petugas Kesehatan dan Pola Asuh Ibu yang Bekerja dengan Tumbuh Kembang Bayi di Klinik Pratama Sunggal - Aulia , Marshanda Putri; Sephira, Intan Nadya; Sinaga , Jesika Kristin; Sembiring , Juni Kristiani Br; Sidabutar , Liontin; Paninsari, Debora (Journal of Pharmaceutical and Sciences, 2025)
Background: Infant growth and development during the first 0-12 months represents a crucial phase with long-term impacts on quality of life. Environmental factors, working mothers' childcare practices, and healthcare providers' roles serve as key determinants influencing this process. The risk of developmental delays significantly increases for infants in less supportive environments or those receiving inadequate stimulation. Objective: To analyze the influence of environmental conditions, working mothers' childcare practices, and healthcare providers' roles on the growth and development of infants aged 0-12 months at Sunggal Primary Clinic. Methods: This observational analytical study employed a cross-sectional design involving 35 subjects selected through total sampling. Data collection utilized structured questionnaires and was analyzed using chi-square tests. Results: Statistical analysis revealed significant relationships between environmental conditions and child development (p=0.000, with 62.9% supportive environments), between healthcare providers' roles and development (p=0.000, with 60% adequate services), and between working mothers' childcare practices and development (p=0.000, with 57.1% optimal practices). Conclusion: All three variables significantly influence infant growth and development, indicating the need for an integrated approach to optimize these contributing factors.